Family Issues. Difficulties in Migrant Family Life Exacerbated by the Pandemic - Tumminelli, Giuseppina (Italian Sociological Review, 2022)
Most of the time, when we talk about the family, we think of the indigenous family, but what happens when the focus shifts to foreign families? Furthermore, in a time of pandemic, what repercussions and impacts have there been on foreign families? And have the interventions proposed by the government to deal with COVID-19 and to support families, taken foreign families into account? The issue is quite complex because it has to deal, on the one hand, with definitional problems related to the difficulties in identifying types of foreign families (Ambrosini, 2020b) present in Italy, and, on the other hand, with an analysis of the impact that the virus has had on family structures. Migrant families represent heterogeneous contexts where there is constant, dynamic interaction between structural dimensions, cultural aspects and subjective choices, and during the pandemic, these have become “families in the balance”, vulnerable actors, subjected to extreme marginality. There are many issues, such as the home, which, for example, has become a space/place where to spend one’s time and experiment with forms of smart working, but many of the homes where migrant families live are not organised to cope with the pandemic and often reflect a pronounced inequality. [...]